Metabolic screening in primary care for patients with schizophrenia or schizoaffective disorder and taking antipsychotic medication - Ross Lawrenson; Sophie Scarlet; Ruzaimah Mohammed; Kee Ping Lim; Shivam Deo; Abhijit Bhat; Muhammad Asim; Chunhuan Lao; Sally Carter; Joanna Ly; Lynne Chepulis; Rawiri Keenan (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONLife expectancy in patients with schizophrenia is 15-20 years less than the general population. A dominant cause of morbidity and mortality in these patients is cardiovascular disease. Adverse consequences of modifiable cardiovascular risk factors can be reduced by regular monitoring of metabolic outcomes and intervention if required. AIMTo evaluate the metabolic screening in primary care for patients with schizoaffective disorders managed in primary care. To show the usefulness of combining simple practice audits in evaluating such areas of clinical practice. METHODSAn audit was undertaken in eight general practices in the Waikato and Bay of Plenty regions of New Zealand. Specifically, the monitoring of patients with schizophrenia or schizoaffective disorder whose antipsychotic medication was prescribed by primary care doctors was audited. Patient monitoring was compared to the guideline recommendation of the Royal Australian and New Zealand College of Psychiatrists (RANZCP) and the Best Practice Advisory Centre (BPAC). RESULTSIn total, 117 patients were included in the audit and none were fully monitored, as recommended by the RANZCP guidelines. Although two-thirds of patients had been evaluated for glycosylated haemoglobin (HbA1c), lipids, blood pressure, complete blood count and weight, <10% of patients had had prolactin, waist circumference or electrocardiogram measurements recorded. The proportion of patients having a HbA1c measured was also significantly higher in younger patients and patients who were non-Māori or enrolled with an urban practice (all P<0.05). When using the simplified BPAC guidelines, half of all patients were correctly monitored. DISCUSSIONThese findings show there is room for improvement in the monitoring of patients receiving antipsychotic medication in primary care. This may indicate the need for clear guidance and general practitioner education around the monitoring requirements of these patients. Alternatively, a more simplified monitoring protocol may need to be developed. This audit has also shown that there is value in several practices completing the same audit and providing a larger cohort of patients for pooled data analysis.